THE RELATIONSHIP BETWEEN SELF EFFICACY AND ACHIEVEMENT IN MATHEMATICS CLASS II AT MI PGM CIREBON CITY - Sabilla Dheani; Dwi Anita Alfiani; Dadan Setiawan (Universitas Pendidikan Indonesia, 2023)
The purpose of this study was to determine the relationship between self -efficacy and student achievement in mathematics class II at MI PGM Cirebon City. The approach used for research is quantitative and the research design uses a correlational research design. The population of this study were class II students of MI PGM Cirebon City. The sampling technique used a saturated sample with 48 students as respondents. The data collection instruments used were questionnaires and documentation. The research data were analyzed through normality tests, unilinearity tests, and hypothesis testing using SPSS version 16.0 for windows. The results showed that the self-efficacy of class II students at MI PGM Cirebon City was in the moderate category. It is known that as many as 48 respondents with a percentage of 60.4% have self-efficacy and as many as 1 respondent with a presentation of 2.1% have self- efficacy. Learning achievement in class II mathematics at MI PGM Cirebon City, it can be concluded that having good learning achievement in mathematics subjects, shows a presentation of 79.2%. relationship between self-efficacy and student achievement in class II mathematics at MI PGM Cirebon City.